Pengaruh Penerapan Model Discovery Learning Terhadap Hasil Belajar Peserta Didik Pada Materi Ekosistem Kelas X Di SMA Negeri 13 samarinda - Shafira Salsabila Indipravita; Akhmad Akhmad; Sri Purwati; Ruqoyyah Nasution; Suparno Putera Makkadafi (PendIPA Journal of Science Education, 2026)
The Effect of the Discovery Learning Model on Student Learning Outcomes in Ecosystems for Grade X Students at SMA Negeri 13 Samarinda." Thesis. Bachelor's Degree in Biology Education, Faculty of Teacher Training and Education, Mulawarman University. This research was supervised by Dr. H. Akhmad, M.Kes, as my first supervisor. This research is motivated by the low learning outcomes of class X students of SMA Negeri 13 Samarinda in biology subjects. In addition, the application of various learning models so that students tend to be passive, thus triggering low student creativity. Aims to determine the effect of the Discovery Learning learning model on student learning outcomes in ecosystem material. The method used is a quasi-experiment (Quasi Experiment) using two classes. With a pretest-posttest control group design research design. The population is class X students of SMA Negeri 13 Samarinda, sampling using Purposive sampling technique. Two classes were selected, namely class X-8 as the experimental class and class X-7 as the control class. The data analysis technique used is the Independent Sample t Test with a significance level of 5%. The results of the data analysis Sig. <0.05 (0.000 <0.05) then H0 is rejected and Ha is accepted. The use of the Discovery Learning learning model has a significant effect on student learning outcomes in class X ecosystem material at SMA Negeri 13 Samarinda (Sig. 0.000 <0.05). Apart from that, it has also been proven to be able to significantly improve student learning outcomes, as shown by an increase in the average score from the low category (43.33) to high (80).